Fertility preserving surgery for high-grade epithelial ovarian carcinoma confined to the ovary. (May 2020) - Nasioudis, Dimitrios; Mastroyannis, Spyridon A.; Haggerty, Ashley F.; Giuntoli, Robert L.; Morgan, Mark A.; Ko, Emily M.; Latif, Nawar A.
Abstract: Objective: To investigate the safety of uterine preservation in patients with high-grade epithelial ovarian carcinoma (EOC). Study design: The Surveillance, Epidemiology, and End Results database was accessed (1988–2014) and patients aged < = 45 years, diagnosed with an unilateral high-grade non-clear cell EOC confined to the ovary were selected. Based on surgery codes we determined whether hysterectomy was performed. Overall (OS) and cancer-specific survival (CSS) was estimated calculated following generation of Kaplan-Meier curves and compared using the log-rank test. Cox hazard model was constructed to control for possible confounders. Results: A total of 1039 patients with a median follow-up of 119 months were identified. Rate of uterine preservation was 31.8 %. Patients who had hysterectomy were older (median 41 vs 32 yrs, p < 0.001). Patients with mucinous tumors were less likely to undergo hysterectomy (58.9 %) compared to those with endometrioid (73.9 %) and serous (75.9 %) carcinoma, p < 0.001. There was no difference in CSS between patients who did and did not have hysterectomy, p = 0.70 (5-yr rates were 93.9 % vs 92.2 %, respectively). After controlling for year of diagnosis, tumor histology (serous vs non-serous), disease stage, performance of lymph node dissection (LND) and tumor grade, uterine preservation was not associated with a worse cancer-specific (HR: 1.08, 95 % CI:0.69, 1.71) and overall (HR:0.88, 95 % CI: 0.59, 1.32) mortality. Conclusion: In this retrospective cohort of patients with unilateral high-grade non-clear cell EOC confined to the ovary, uterine preservation was not associated with a worse prognosis.